Structural, energetic, and dynamic responses of the native state ensemble of staphylococcal nuclease to cavity‐creating mutations. Issue 6 (27th April 2013) - Roche, Julien; Caro, Jose A.; Dellarole, Mariano; Guca, Ewelina; Royer, Catherine A.; García‐Moreno E., Bertrand; Garcia, Angel E.; Roumestand, Christian
Abstract: The effects of cavity‐creating mutations on the structural flexibility, local and global stability, and dynamics of the folded state of staphylococcal nuclease (SNase) were examined with NMR spectroscopy, MD simulations, H/D exchange, and pressure perturbation. Effects on global thermodynamic stability correlated well with the number of heavy atoms in the vicinity of the mutated residue. Variants with substitutions in the C‐terminal domain and the interface between α and β subdomains showed large amide chemical shift variations relative to the parent protein, moderate, widespread, and compensatory perturbations of the H/D protection factors and increased local dynamics on a nanosecond time scale. The pressure sensitivity of the folded states of these variants was similar to that of the parent protein. Such observations point to the capacity of the folded proteins to adjust to packing defects in these regions. In contrast, cavity creation in the β‐barrel subdomain led to minimal perturbation of the structure of the folded state, However, significant pressure dependence of the native state amide resonances, along with strong effects on native state H/D exchange are consistent with increased probability of population of excited state(s) for these variants. Such contrasted responses to the creation of cavities could not be anticipated from global thermodynamic stability or crystal structures; they depend on the local structural and energetic context of the substitutions. © 2012 Wiley Periodicals, Inc.